2020
DOI: 10.2139/ssrn.3649953
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of School Closures and Other Pre-Lockdown COVID-19 Mitigation Strategies in Argentina, Italy, and South Korea

Abstract: The rapid spread of COVID-19 forced policy-makers to swiftly find solutions to reduce infection rates and keep mortality as low as possible. Empirical analyses on the effectiveness of control measures are hereby of primary importance. School closures were among the earliest measures enacted by the governments of most countries. However, while schools are now reopening in many countries, the impact of school closures on the course of the epidemic is still an open question. Adopting parametric and non-parametric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 55 publications
0
47
0
Order By: Relevance
“…Included studies are described in Table 1. All studies [13][14][15][16][17][18][19][20][21][22] reported the effect of school closures on community transmission of SARS-CoV-2, and one study 21 additionally examined school re-opening. All studies used data from national Government sources or international data repositories, and reported on the first half of 2020.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Included studies are described in Table 1. All studies [13][14][15][16][17][18][19][20][21][22] reported the effect of school closures on community transmission of SARS-CoV-2, and one study 21 additionally examined school re-opening. All studies used data from national Government sources or international data repositories, and reported on the first half of 2020.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies specifically sought to estimate an effect of school closures on SARS-CoV-2 transmission. [13][14][15]17,18,21 The remaining four studies primarily sought to estimate the effect of NPIs (but reported an independent estimate for school closures within their analysis) . 16,19,20,22 Several analytic approaches were used, including: various types of regression models (n-7), 13,14,[16][17][18][19][20]22 time series analysis with Bayesian inference (n=1), 15 comparison to a synthetic control group derived from data from comparable countries (n=1), 18 and presentation of an epidemic curve 21 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations